First-principles study of the solute segregation in twin boundaries in Mg and possible descriptors for mechanical properties. (5th March 2019) - Pei, Zongrui; Li, Rui; Nie, Jian-Feng; Morris, James R.
Abstract: Twin boundaries play an important role in shaping the mechanical properties of Mg and Mg alloys. In this study, we simulate the segregation energies (SEs) of 23 solutes in the profuse 10 1 ¯ 2 and 10 1 ¯ 1 twin boundaries in Mg. Almost all solutes have both negative and positive SEs (except Tl), which indicate these solutes prefer to segregate at half of the sites in the twin boundaries. The correlation between the signs of SEs and the solute sites is a strong indication for the importance of the volumetric effects, which is confirmed by our modeling based on Voronoi volume calculations. In order to quantitatively describe the solute segregation, solute coverages of the two twin boundaries are calculated using the Langmuir-McLean model. Convergence tests are performed in order to obtain accurate solute coverages. The converged solute coverages are employed as descriptors for the solute strengthening through twin boundaries. Finally, we show two "treasure maps" for the materials design based on descriptors originated from solute solution effects at twin boundaries and stacking faults. Graphical Abstract: Highlights: Possible descriptors for mechanical properties of Mg are identified. The segregation energies of 23 solutes in both the compression and tensile twin boundaries are calculated and modeled. The mechanical contributions to segregation energies determine the mathematic signs of the latter.